1980
DOI: 10.1128/jb.142.3.939-944.1980
|View full text |Cite
|
Sign up to set email alerts
|

Oligoglucuronide production in Mucor rouxii: evidence for a role for endohydrolases in hyphal extension

Abstract: Culture filtrates of Mucor rouxii contained oligomers of glucuronic acid which were labeled rapidly during pulses with D-[U-'4C]glucose. These oligomers were probably derived by enzymatic lysis of acidic polymers in the cell wall. The kinetics of the incorporation of label into oligouronides and cell wall polymers suggested that lysis of the wall was required for active hyphal extension. Experiments with cycloheximide, which inhibited hyphal extension, suggested that wall lysis was also required for the subapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Whereas Bartnicki-Garcia and Ruiz-Herrera have looked to the chitin-chitosan microfibrillar skeleton of the Mucor cell wall for the key to explaining dimorphism, Dow, Villa, and colleagues have focused on the polyuronide matrix components of the wall in search of correlates with morphogenesis (57,60,61). It is an entirely reasonable proposition that the properties of the mortar may be as important as those of the brick in defining the potential architecture of an edifice.…”
Section: Composition and Construction Of The Cell Wall In Mucor Yeastmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas Bartnicki-Garcia and Ruiz-Herrera have looked to the chitin-chitosan microfibrillar skeleton of the Mucor cell wall for the key to explaining dimorphism, Dow, Villa, and colleagues have focused on the polyuronide matrix components of the wall in search of correlates with morphogenesis (57,60,61). It is an entirely reasonable proposition that the properties of the mortar may be as important as those of the brick in defining the potential architecture of an edifice.…”
Section: Composition and Construction Of The Cell Wall In Mucor Yeastmentioning
confidence: 99%
“…Pulse-chase experiments employing D-['4C]glucose as label have shown that radioactive oligoglucuronides quickly appear in the supernatant fluid of Mucor cultures. The kinetics of label incorporation into soluble oligoglucuronides and cell wall polymers suggested that ongoing wall lysis is necessary for active hyphal extension (61). Radiolabeled polyuronides and glycoproteins with compositions similar to those of these polymers as they occur in the cell wall appear in membrane fractions of M. rouxii but are rapidly lost from these fractions following a chase.…”
Section: Composition and Construction Of The Cell Wall In Mucor Yeastmentioning
confidence: 99%
“…Uronic acid was measured by the carbazole method as described by Bitter and Muir (9) as the standards. Scintillation counting was performed as described previously (12). Sugars on paper chromatography were detected by the alkaline silver nitrate method (18).…”
Section: Molecular Weight Determinadon a Spinco Model Ementioning
confidence: 99%
“…In this case, the alkaline extraction solubilized only 26.8% of the radioactivity incorporated. It has been reported for fungal cells that cycloheximide inhibits the synthesis of glycoprotein as well as that of proteins but does not have shortterm effects on polysaccharide synthesis (3,4,9). Thus, the radioactivity present in the alkaline extract of cycloheximide-treated cells probably represented polysaccharides from the cell wall matrix (i.e., the mucoran fraction).…”
mentioning
confidence: 93%
“…More than 56% of the radioactivity incorporated in the absence of cycloheximide could be extracted by mild alkaline treatment. This extraction procedure solubilizes most of the cell protein (7) and the cell wall matrix material (3). The remainder of the label was found in glycogen (fraction 1I) and in the cell wall residue (final residue).…”
mentioning
confidence: 99%